2009
DOI: 10.1186/1471-2407-9-464
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of contact inhibition in human glioblastoma cell lines after MIF knockdown

Abstract: BackgroundStudies of the role of the cytokine macrophage-migration-inhibitory-factor (MIF) in malignant tumors have revealed its stimulating influence on cell-cycle progression, angiogenesis and anti-apoptosis.ResultsHere we show that in vitro targeting MIF in cultures of human malignant glioblastoma cells by either antisense plasmid introduction or anti-MIF antibody treatment reduced the growth rates of tumor cells. Of note is the marked decrease of proliferation under confluent and over-confluent conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 37 publications
1
25
0
3
Order By: Relevance
“…(S,R)-3-(4-hydroxyphenyl)-4,5-dihydro-5-isoxazole acetic acid methyl ester (ISO-1), which has been used for the treatment of various inflammatory diseases, was reported to be an inhibitor of the biological activity of MIF [42]. Subsequent to our report[12], in vitro MIF inhibition experiments have been conducted using small molecules for various cancers, such as colon cancer inhibited by ISO-1 [43], prostate cancer inhibited by ISO-1 [44], lung cancer inhibited by ISO-1 [45], and 4-Iodo-6-phenylpyrimidine (4-IPP) [45], glioblastoma inhibited by ISO-1[46-48], and adenoid cystic carcinoma inhibited by ISO-1[49]. In addition, several experiments have been conducted on animal models ( in vivo ) such as those for colorectal cancer inhibited by ISO-1 [50], and prostate cancer inhibited by ISO-1 [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(S,R)-3-(4-hydroxyphenyl)-4,5-dihydro-5-isoxazole acetic acid methyl ester (ISO-1), which has been used for the treatment of various inflammatory diseases, was reported to be an inhibitor of the biological activity of MIF [42]. Subsequent to our report[12], in vitro MIF inhibition experiments have been conducted using small molecules for various cancers, such as colon cancer inhibited by ISO-1 [43], prostate cancer inhibited by ISO-1 [44], lung cancer inhibited by ISO-1 [45], and 4-Iodo-6-phenylpyrimidine (4-IPP) [45], glioblastoma inhibited by ISO-1[46-48], and adenoid cystic carcinoma inhibited by ISO-1[49]. In addition, several experiments have been conducted on animal models ( in vivo ) such as those for colorectal cancer inhibited by ISO-1 [50], and prostate cancer inhibited by ISO-1 [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, the cancer cell growth assay is not the first report of the use of MIF or SCD1 inhibitors to retard cancer cell growth. MIF or SCD1 inhibitors have been used to restrict the growth or metastasis of many types of cancers [43-48,56-60], although not STS. Moreover, gene silencing of MIF or SCD1 has been carried out for many kinds of cancers [44,48,54,59-67], again with the exception of STS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review of the literature identified 3 main pathways that may be targets of therapy (see Figure ). First, some inhibitors of MIF (S,R‐3‐(4‐hydroxyphenyl)‐4,5‐dihydro‐5‐isoxazole acetic acid methyl ester and 4‐IPP) have already shown a therapeutic effect on cell proliferation in many cancers (ie, HNSCC, glioma, and colorectal adenocarcinoma) . Other studies conducted on leukemia, lymphoma, and prostate and ovarian cancers have also shown the possible clinical benefits of such therapeutic strategies.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Hypoxia-Inducible Factor 1-alpha HAGEMANN, 2013;DOUGLAS et al, 2004;DUFFY et al, 2008;FELLER;ALTINI;LEMMER, 2013;HAMATAKE et al, 2008;HATHAWAY et al, 2005;MANTOVANI;GARLANDA;ALLAVENA, 2010;MURAMAKI et al, 2006;TAKES et al, 2008) O FANG et al, 2008;KAMIMURA et al, 2000;MOHRI et al, 2009;REN et al, 2005;TOMIYASU et al , 2002;XIA et al, 2005;YASASEVER et al, 2007) DENZ et al, 2010;KROCKENBERGER et al, 2010;LEE et al, 2008;LI et al, 2009;MCCLELLAND et al, 2009;RENDON et al, 2009;SCHRADER et al, 2009;SUN et al, 2005;VERJANS et al, 2009, WU et al, 2009 Alguns dos mecanismos pelos quais a MIF induz o desenvolvimento tumoral estão associados às vias Phosphoinositide 3-Kinase/protein kinase B (PI3K/AKT), Retinoblastoma/Early-region-2 transcription factor (Rb/E2F),…”
Section: Hif-1αmentioning
confidence: 99%